Direct infussion Electrospray Mass Spectrometry as a new non-invasive tool for serum metabolomics in induced-stress subjects - Lorenzo-Tejedor, Mónica; Cámara, Concepción de la; Lopez-Anton, Raul; Bailon, Raquel; Aguiló, Jordi; Bernal Ruiz, María Luisa (The European journal of psychiatry, 2015)
Background and Objectives: Nanotechnology is becoming a tool for the study of changes in the metabolome of patients in different states of disease. Analytical techniques such as Electrospray Mass Spectrometry, allow to find biomarkers by determination of metabolites. Nowadays, there is not an objective analytical approach for diagnosis of stress. Thus, the objectives of this pilot work are: Describing the development of a fast, direct and non-invasive analytical protocol, applied for the first time, to study the metabolomic profile of patient´s different states through a disease. Testing the protocol in a pilot sample with non-stressed and stress-induced subjects. Methods: High resolution direct infusion electrospray mass spectrometry has been used to analyse the metabolome of blood samples (0.3 ml) from six subjects. Results: Data prove a clear discrimination between non-stressed and stressed states in the metabolome. Data showed different predominant metabolites in both states. Results allow objective characterization of the state of the patient. Conclusions: Although this is a pilot study, the method was successful in discriminating different metabolites in non-stressed and stress-induced subjects.